Physical Entities as Spatial Creations: A Theory of Spatial Evolution - Hamidi, Nabil (no, 2025)
Space is traditionally treated as a geometric background, yet all empirical observations from cosmology and physics indicate that space is a dynamic physical medium. This article argues, using evidence from observational cosmology, quantum field theory, chemistry, evolutionary biology, and systems science, that space evolves and transforms into all physical, biological, and social systems. Matter emerges through phase transitions in spatial fields (Guth, 1997; Kolb & Turner, 1990). Chemical structure is reducible to spatial electron distributions (Atkins & de Paula, 2017). Biological systems depend on spatial gradients and boundaries (Alberts et al., 2022). Communication processes require spatial separation (Shannon, 1948). Political and social systems arise from the spatial distribution of human populations (Wendt, 1999; Buzan & Little, 2000). No empirical evidence contradicts this continuity. The conclusion is that space is the original evolving substrate, and all systems are transformations of spatial structure.
Evolutionary Theory of Space: How Space Evolves into All Physical Systems